No more police: a case for abolition - Kaba, Mariame (The New Press, 2022)
Cops don't stop violence -- We are survivors -- Re-form -- No soft police -- How do we get there? Toward a police free future -- Tricks and tensions -- Experiment and build -- Black feminist musings.